A rare case of metastatic renal carcinoid - Kato, Yoshiharu (BioMed Central, 2010)
BACKGROUND: Carcinoid is an endocrine cell tumor with low-grade atypia, which is generally a low-grade malignant cancer with a good prognosis. Metastatic renal carcinoid is even rarer than primary carcinoids. CASE PRESENTATION: We present our experience of a patient with metastatic renal carcinoid from the gastrointestinal tract. CONCLUSIONS: The carcinoid tumor of the kidney in our patient, who had a history of liver metastasis from rectal carcinoid, was considered metastatic based on the pathological findings.